Activity of Mangrove-Derived Fusarium equiseti 20CB07RF Extract Against Clinical, Antibacterial-Resistant Pseudomonas aeruginosa - Bahri, Syaiful; Setiawan, Wawan Abdullah; Setiawan, Fendi; Lutfiah, Rosyidatul; Juliasih, Ni Luh Gede Ratna; Ambarwati, Yuli; Ahmadi, Peni; Arai, Masayoshi; Hendri, John; Hadi, Sutopo; Setiawan, Andi (Science and Technology Indonesia, 2024)
Endophytic fungi originating from mangroves are potential sources of secondary metabolites with varying bioactivities. This research explores the bioactive metabolites produced by endophytes derived from mangrove plants. Endophytic fungi were collected from various parts of several mangrove plants (roots, stems, and leaves, as well as the surrounding mud). A total of 17 endophytics fungi were obtained. The isolates were derived from the leaves (1 isolate), stems (8 isolates), roots (5 isolates), and surrounding mud (3 isolates). A single fungal colony was cultured using solid-state fermentation for 14 days. The fermented fungal biomass was extracted using ethyl acetate (EtOAc) and evaluated for its antibacterial activity against clinical pathogenic bacteria. In the preliminary screening, the EtOAc extract of the CB07RF1 isolate exhibited notable growth-inhibitory effects against Pseudomonas aeruginosa. The isolate was verified by molecular identification using a study of the rDNA internal transcribed spacer (ITS) sequence, revealed that isolate CB07RF1 was very similar to Fusarium equiseti (99% similarity). Isolate 20CB07RF1, obtained by solid-state fermentation using a rice medium indicated as peptide compound group, and featured active components that exhibited potent growth inhibitory activity against Pseudomonas aeruginosa at a concentration of 12.5 mg/mL. This study demonstrates, for the first time, that Fusarium equiseti extracts grown in a rice medium contain antimicrobial compounds that can inhibit the growth of P. aeruginosa, an important clinical pathogen known for its antibacterial resistance. These findings accent mangrove endophytic fungi as important sources of bioactive compounds and will advance related research in the fields of biotechnology, pharmacology, and life sciences.